PENGARUH VARIASI LAMA PENYIMPANAN LARUTAN TURK MODIFIKASI AIR PERASAN JERUK NIPIS (Citrus Aurantifolia) TERHADAP HITUNG JUMLAH LEUKOSIT - hanipa sapria; Norlaila Puteri Maulida; Ratna Amanah Sari; Putri Kartika Sari (LPPM Universitas Abdurrab, 2024)
The availability of Turk reagents for manual leukocyte count examinations, commonly performed by simple clinics or remote health centers, is often limited. This limitation can arise due to depletion or expiration of the reagents. Consequently, many researchers have sought to address this issue by developing modified Turk solutions, including those utilizing freshly squeezed lime juice, although the quality of these alternative reagents remains untested. This study aims to investigate the effects of storing modified Turk solutions with lime juice (Citrus aurantifolia) at room temperature for 1 day, 7 days, and 14 days on leukocyte count. This experimental research employed a Post Test Only Control Group Design, with variations in storage duration 1, 7, 14 days replicated 12 times and analyzed statistically. The mean leukocyte counts were 6.083 cells/mm3 at 1 day, 7.612 cells/mm3 at 7 days, and 6.304 cells/mm3 at 14 days, while the control exhibited a count of 7.675 cells/mm3. The results of the ANOVA and LSD tests indicated significant differences in the leukocyte counts between day 1 and day 14 with the control Turk, whereas day 7 did not show such differences, however, the interpretation of the leukocyte count results for the lime-modified Turk solution on days 1, 7, and 14 still indicated compliance with the reference values, i.e., 4,000-10,000 cells/mm3.